2018
DOI: 10.5465/annals.2016.0044
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Level Process Model for Understanding Diversity Practice Effectiveness

Abstract: The issue of workforce diversity has been at the forefront of organizational concerns for many years. Not surprisingly, this topic has generated reams of research aimed at shedding light not only on the challenges involved, but also on ways these challenges have been and can be addressed. This paper reports on a comprehensive survey of the most recent studies in an effort to uncover what has been learned and what remains to be examined. While the paper is aimed primarily at researchers, it also offers a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
158
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 133 publications
(172 citation statements)
references
References 161 publications
5
158
0
1
Order By: Relevance
“…Third, bridging organization‐level and individual‐level research (Nishii et al, ), our multilevel and multisource model empirically supports the top‐down effect linking organization‐reported formal diversity management programs, employees' shared perceptions of formal diversity management programs, and employees' individual psychological and attitudinal reactions. Our study captures the integrated process of how an HR system functions, from what organizations do to what employees perceive (Arthur & Boyles, ), and then to how employees react (Nishii et al, ). Understanding this complete process will help researchers to identify critical variables and decisions at each stage.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Third, bridging organization‐level and individual‐level research (Nishii et al, ), our multilevel and multisource model empirically supports the top‐down effect linking organization‐reported formal diversity management programs, employees' shared perceptions of formal diversity management programs, and employees' individual psychological and attitudinal reactions. Our study captures the integrated process of how an HR system functions, from what organizations do to what employees perceive (Arthur & Boyles, ), and then to how employees react (Nishii et al, ). Understanding this complete process will help researchers to identify critical variables and decisions at each stage.…”
Section: Discussionsupporting
confidence: 71%
“…This study highlights several action steps HR professionals can take to make their organizations more inclusive. Past research has consistently demonstrated the value of positive diversity climates but was unable to deliver clear and specific recommendations to HR professionals on “which diversity practices should be used, how they should be implemented, for what purpose, and to what effect” (Nishii et al, , p. 38). Most research evidence supports the adoption of identity‐blind HR practices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations